2008
DOI: 10.1152/ajpregu.90650.2008
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase contributes to renal damage and dysfunction in Dahl salt-sensitive hypertension

Abstract: The goal of this study was to test the hypothesis that NADPH oxidase contributes importantly to renal cortical oxidative stress and inflammation, as well as renal damage and dysfunction, and increases in arterial pressure. Fifty-four 7- to 8-wk-old Dahl salt-sensitive (S) or R/Rapp strain rats were maintained for 5 wk on a high sodium (8%) or high sodium + apocynin (1.5 mmol/l in drinking water). Arterial and venous catheters were implanted on day 21. By day 35 in the high-Na S rats, mRNA expression of renal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 49 publications
5
47
3
1
Order By: Relevance
“…The rise in arterial blood pressure in response to increased dietary salt intake in the MnSOD-deficient mice was accompanied by upregulation of NAD(P)H oxidase which is a major source of non-mitochondrial superoxide production in the renal and cardiovascular tissues. Upregulation of NAD(P)H oxidase in the kidney and vascular tissues is a common feature of nearly all models of acquired and hereditary hypertension [15][16][17][18]. Therefore, finding elevated renal tissue NAD(P)H oxidase in this model is consistent with that observed in other models of hypertension.…”
Section: Discussionsupporting
confidence: 87%
“…The rise in arterial blood pressure in response to increased dietary salt intake in the MnSOD-deficient mice was accompanied by upregulation of NAD(P)H oxidase which is a major source of non-mitochondrial superoxide production in the renal and cardiovascular tissues. Upregulation of NAD(P)H oxidase in the kidney and vascular tissues is a common feature of nearly all models of acquired and hereditary hypertension [15][16][17][18]. Therefore, finding elevated renal tissue NAD(P)H oxidase in this model is consistent with that observed in other models of hypertension.…”
Section: Discussionsupporting
confidence: 87%
“…NADPH oxidase contributes importantly to renal cortical oxidative stress, inflammation, renal damage and dysfunction and increased in arterial pressure. 63 Previous study showed that the primary source of ROS generation in the renal cortex is NADPH oxidase. 64 NADPH oxidase is a cytoplasmic enzyme consisting of at least one catalytic, transmembrane-spanning NOX subunit, which produces ROS by transferring electrons from NADPH to molecular oxygen.…”
Section: 50mentioning
confidence: 99%
“…63 In conclusion, antioxidant NAC can confer protection against nitrosative and oxidative stresses in renal tissue induced by holoxan by suppressing renal NADPH oxidase activation, MDA, nitric oxide and restoring or enhancing SOD enzyme activity. Thus, inhibition of NADPH oxidase elevation level and activation led to subsequent reduction of ROS production and subsequently might effectively improve the gonadal hormone disturbance, sexual and reproductive functions.…”
mentioning
confidence: 91%
“…35 In the same rat model, an NADPH inhibitor, apocynin, also showed significant attenuation of proteinuria, as well as a significant reduction of SBP. 36 In this study, the significant reduction of p22 phox by combination therapy with irbesartan and efonidipine compared with irbesartan monotherapy may have contributed to the significant hypotensive effects seen with combination therapy compared with irbesartan alone.…”
Section: Discussionmentioning
confidence: 76%